Comparison of apnoeic oxygen techniques in term pregnant subjects: a computational modelling study. (October 2022) - Ellis, Reena; Laviola, Marianna; Stolady, Daniel; Valentine, Rebecca L.; Pillai, Arani; Hardman, Jonathan G.
Abstract: Background: Hypoxaemia during general anaesthesia can cause harm. Apnoeic oxygenation extends safe apnoea time, reducing risk during airway management. We hypothesised that low-flow nasal oxygenation (LFNO) would extend safe apnoea time similarly to high-flow nasal oxygenation (HFNO), whilst allowing face-mask preoxygenation and rescue. Methods: A high-fidelity, computational, physiological model was used to examine the progression of hypoxaemia during apnoea in virtual models of pregnant women in and out of labour, with BMI of 24–50 kg m −2 . Subjects were preoxygenated with oxygen 100% to reach end-tidal oxygen fraction (FE'O2 ) of 60%, 70%, 80%, or 90%. When apnoea started, HFNO or LFNO was commenced. To simulate varying degrees of effectiveness of LFNO, periglottic oxygen fraction (FgO2 ) of 21%, 60%, or 100% was configured. HFNO provided FgO2 100% and oscillating positive pharyngeal pressure. Results: Application of LFNO (FgO2 100%) after optimal preoxygenation (FE'O2 90%) resulted in similar or longer safe apnoea times than HFNO FE'O2 80% in all subjects in labour. For BMI of 24, the time to reach SaO2 90% with LFNO was 25.4 min (FE'O2 90%/FgO2 100%) vs 25.4 min with HFNO (FE'O2 80%). For BMI of 50, the time was 9.9 min with LFNO (FE'O2 90%/FgO2 100%) vs 4.3 min with HFNO (FE'O2 80%). A similar finding was seen in subjects with BMI ≥40 kg m −2 not in labour. Conclusions: There is likely to be clinical benefit to using LFNO, given that LFNO and HFNO extend safe apnoea time similarly, particularly when BMI ≥40 kg m −2 . Additional benefits to LFNO include the facilitation of rescue face-mask ventilation and ability to monitor FE'O2 during preoxygenation.